Ischemic Heart Disease and Work Disability in Patients Treated at the Internal Medicine Consultation and Assessed by the Expert Medical Labor Commission - Belkis Vicente Sánchez; Ernesto Vicente Peña; Tania Cuellar Torres; Miriam Costa Cruz (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Background: ischemic heart disease represents a major challenge given the large number of people affected by this condition, its increasing contribution to overall mortality, the frequent disability resulting from it, and the complexity and high cost of its treatment. Objective: to describe the work disability caused by ischemic heart disease in patients treated at the internal medicine consultation and assessed by the Expert Medical Labor Commission of Cienfuegos municipality. Methods: a cross-sectional study was conducted including all patients with ischemic heart disease treated at the internal medicine consultation and assessed by the Expert Medical Labor Commission of Cienfuegos municipality from October 2012 to July 2013. The variables analyzed were: age, sex, occupation, years of work and accrued salary, clinical diagnosis, length of time the condition had been present and associated chronic diseases; existence of prior assessment by an Expert Medical Labor Commission and decision reached, previous days of sick leave and current decision of the commission. The data were analyzed using SPSS (version 18.0) and the results are shown in tables and graphs as numbers and percentages. Results: a predominance of men was observed. Forty two point nine percent were service workers and the average number of years of work was 24.60. Forty two point nine percent were previously assessed by the commission. Two hundred one point thirteen days of sick leave were granted and social security expenditure in a month was high. Diabetes mellitus was the most common chronic disease followed by hypertension, obesity and dyslipidemia. Of the workers previously assessed, half received permanent and temporary disability benefits. Conclusions: ischemic heart disease causes different degrees of disability. Its costs in terms of social security are increasing.